Ferrochelatase Structural Mutant ( Fech m1Pas) in the House Mouse - Boulechfar, Samia; Lamoril, Jérôme; Montagutelli, Xavier; Guenet, Jean-Louis; Deybach, Jean-Charles; Nordmann, Yves; Dailey, Harry; Grandchamp, Bernard; de Verneuil, Hubert (Genomics (San Diego, Calif.), 1993)
The molecular basis of an inherited defect of ferrochelatase in mouse ( Fech m1Pas/Fech m1Pas , described by Tutois et al., 1991, J. Clin. Invest. 88: 1730-1736) was investigated. cDNA clones encoding ferrochelatase, isolated by amplification of the mRNA from the liver of a mutant mouse using the polymerase chain reaction, were sequenced by the dideoxynucleotide chain-termination method. All the clones carried a T to A transversion at nucleotide 293, leading to a methionine to lysine substitution at position 98 in the protein (mutation M98K). Hybridization with allele-specific oligonucleotides (ASOs) confirmed the mutation at the cDNA and genomic levels. Finally, expression of the mutant ferrochelatase protein in E. coli demonstrated a marked deficiency in activity in agreement with the activity of the deficient enzyme in vivo. This Fech m1Pas/Fech m1Pas mutant mouse represents a useful model for studying the pathophysiological feature of the human disease and the first accessible model for gene therapy in the field of porphyrias.